Documenta Fifteen : Handbook : english. - Schmidt, Petra; Schlüter, Ralf (Berlin : Hatje Cantz Verlag, 2022)
*foundationClass*collective ; Pmtoh, Agus Nur Amal ; Yard, Alice ; Patil, Amol K ; Another Roadmap Africa Cluster ; Archives des luttes des femmes en Algérie ; Arts Collaboratory ; Asia Art Archive ; Atis Rezistans / Ghetto Biennale ; Baan Noorg Collaborative Arts and Culture ; Black Quantum Futurism ; BOLOHO ; Britto Arts Trust ; Minghao, Cao & Jianjun, Chen ; Centre d'art Waza ; En-Man, Chang ; Chimurenga ; Cinema Caravan and Takashi Kuribayashi ; Perjovschi, Dan ; Warcha, El ; Beltrán, Erick ; FAFSWAG ; Fehras Publishing Practices ; Fondation Festival sur le Niger ; Kunsch, Graziela ; Gudskul ; Ahsan, Hamja ; ikkibawiKrrr ; INLAND ; Instituto de Artivismo Hannah Arendt (INSTAR) ; Jatiwangi art Factory ; Jimmi Durham & A Stick in the Forest by the Side of the Road ; Abboud, Jumana Emil ; Keleketla! Library ; Dalena, Kiri ; Komîna Film a Rojava ; La Intermundial Holobiente ; LE 18 ; Arsanios, Marwa ; Más Arte Más Acción ; Thi, Nguyen Trinh ; Nhà Sàn Collective ; Bulling, Nino ; OFF - Biennale Budapest ; Party Office b2b Fadescha ; Öǧrenci, Pinar ; Project Art Work ; Bell, Richard ; Sa Sa Art Projects ; Sada [regroup] ; Ahmed, Safdar ; Ismailova, Saodat ; Serigrafistas queer ; Siwa plateforme - L'Economat at Redeyef ; Phadke, Sourabh ; Subversive Film ; Taring Padi ; The Black Archives ; The Nest Collective ; The Question of Funding ; Trampoline House ; Wajukuu Art Project ; Wakaliga Uganda ; Eid-Sabbagh, Yasmine ; ZK/U - Center for Art and Urbanistics
documenta fifteen, Kassel, June 18 - September 25, 2022
boek